Investigating safety culture in the South African railway industry - Komane, Ofentse Shadi (Rhodes University, 2026)
Embargo applied. Embargo period to expire in October of 2027.
a case study exploring safety culture manifestation in a South African railway operator
Keywords: Uncatalogued